Sleep quality and disturbances in patients with dystrophic epidermolysis bullosa - Giulio Fortuna; Massimo Aria; Sarah Whitmire; Rodrigo Cepeda-Valdes; Maria Guadalupe Moreno Trevino; Julio Cesar Salas-Alanís (Wolters Kluwer Medknow Publications, 2018)
Background: Sleep disturbances in patients with dystrophic epidermolysis bullosa (DEB) have never been investigated and still remain an open question. We sought to examine sleep quality and its relationship with pain and mood disorders in DEB patients. Methods: Twenty-eight DEB patients and 26 healthy individuals completed the following battery of scales: the Pittsburgh Sleep Quality Index (PSQI), the Epworth Sleepiness Scale (ESS), the Medical Outcomes Study (MOS) Sleep Scale, the Visual Analogue Scale (VAS), the Hamilton Rating Scale for Anxiety (HAM-A) and Depression (HAM-D). Linear correlations and hierarchical regression analyses were performed. Results: Patients with DEB have significantly lower scores in daytime sleepiness (p = 0.003) and higher level of pain (p = 0.009) in comparison to controls. The analysis of all PSQI and MOS items failed to demonstrate any statistically significant differences between DEB patients and controls, except for a sub component of PSQI measuring sleep disturbances (p = 0.003). In the study group, a positive correlation was found between PSQI and depressive symptoms (r = 0.56; p = 0.002), anxiety symptoms (r = 0.46; p = 0.015), and pain (r = 0.44; p = 0.020). These results were consistent with the hierarchical regression analysis showing a significant contribution of depression (ΔR2 = 21.8; p = 0.008), anxiety (ΔR2 = 14.5; p = 0.027), and pain (ΔR2 = 13.5; p = 0.032) to poor quality of sleep. Conclusions: DEB patients showed a greater degree of sleep disturbances that can be influenced by depressive symptoms, anxiety symptoms, and pain compared with controls. Therefore, they should be screened for sleep issues that can be possibly impacted by pain and mood disorders.